Use of leucocyte alkaline phosphatase (LAP) score in differentiating malignant from benign paraproteinaemias. Issue 7 (July 1991) - Majumdar, G; Hunt, M; Singh, A K
Abstract : The leucocyte alkaline phosphatase (LAP) score of peripheral blood neutrophils was examined in 20 patients with multiple myeloma and compared with the score in 18 patients with monoclonal gammopathy of undetermined significance (MGUS). The mean (95% confidence limit) LAP score in those with multiple myeloma was 186 (169-218) compared with 92 (64-120) in the MGUS group. In the multiple myeloma group all but one patient had a high LAP score, irrespective of disease. No cause for raised LAP, such as infection, was present in any of the patients with multiple myeloma. In the MGUS group six patients had a raised LAP score; in two of them another cause for such a rise was present (autoimmune haemolytic anaemia and primary thrombocythaemia). In neither group did the LAP score correlate with duration of the disease, bone marrow plasma cell count, paraprotein concentration, haemoglobin, total white cell or neutrophil count. It is concluded that a normal LAP count in patients with paraproteinaemia suggests a benign condition, but a raised count does not indicate a malignant condition.